2019
DOI: 10.7196/sarj.2019.v25i1.239
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii infection in a medical intensive care unit: The impact of strict infection control

Abstract: Background. Acinetobacter baumannii is a waterborne organism that preferentially colonises aquatic environments. Infections usually involve organ systems that have a high fluid content. Multidrug-resistant (MDR) A. baumannii is recognised to be among the most difficult antimicrobial-resistant Gram-negative bacilli to prevent and treat in the nosocomial setting. Objective. To determine the utility of concomitant implementation of a strict antimicrobial stewardship programme and comprehensive infection control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…infection control bundles [42] and associated with an increased risk of death [43,44]. All these findings indicated that the patients, pathogens, and clinical capacity to manage sepsis differ considerably among regions, especially between HIC and LMIC settings, and might explain that our proportions for the ICU and hospital mortality were higher than the rates reported in EPIC III study [37].…”
Section: Plos Onementioning
confidence: 80%
“…infection control bundles [42] and associated with an increased risk of death [43,44]. All these findings indicated that the patients, pathogens, and clinical capacity to manage sepsis differ considerably among regions, especially between HIC and LMIC settings, and might explain that our proportions for the ICU and hospital mortality were higher than the rates reported in EPIC III study [37].…”
Section: Plos Onementioning
confidence: 80%
“…(4, 35, 46-48) Furthermore, Acinetobacter baumannii (17.9%, 45/252; Table S4 as shown in Supplementary file 3), one of the most harmful pathogens, was more frequently isolated from patients in the present study than those from the HIC cohort (4.4%; 137/3113) of the EPIC III study (45). The previous studies showed that Acinetobacter baumannii infection was often due to a lack of strict infection control bundles(49) and associated with an increased risk of death(50, 51). The fact that our proportions for ICU and hospital mortality were higher than those reported in the EPIC III study suggested that patients, pathogens, and clinical capacity to manage sepsis vary significantly between regions, particularly between HIC and LMIC settings.…”
Section: Discussionmentioning
confidence: 99%
“…The patients included in our study were relatively young, since limited ICU resources often require prioritising better prognostic candidates and triaging of patients at the time of admission. Mortality rates of 18.9% [13] and 26.5 per 100 person years [12] were reported from Tygerberg and Groote Schuur hospitals, the largest tertiary hospitals in Cape Town, respectively. This is similar to the mortality rate of 22.2% of patients treated with a combination of colistin and tigecycline in our study, but markedly lower than the 71.4% mortality we found in the colistin monotherapy group.…”
Section: Discussionmentioning
confidence: 99%